Дослідження впливу параметрів механічної активації шихти Ti–C–Al–SiO₂–Al₂O₃–Fe₂O₃–ПТ-НА-01 на тривалість синтезу композиційного матеріалу, що модифікує - Лузан, Сергій Олексійович; Ситников, Павло Андрійович (Харківський національний автомобільно-дорожній університет, 2023)
У роботі досліджено вплив параметрів механічної активації на тривалість синтезу та морфологію шихти Ti–C–Al–SiO₂–Al₂O₃–Fe₂O₃–ПТ-НА-01, призначеної для одержання композиційного матеріалу, що модифікує, отриманого самопоширюваним високотемпературним синтезом. Як вихідні матеріали використано порошки Ti–C–Al–SiO₂–Al₂O₃–Fe₂O₃–ПТ-НА-01. Механічну активацію шихти з варіюванням параметрів оброблення здійснено у розробленому авторами роботи кульовому млині моделі КМ-1, перервного принципу дії з об’ємом робочого сталевого барабана 1,5‧10⁻⁴м³. Маса млина становить 5,8 кг, габарити – (Ш–В–Д) 190–180–230 мм. Тривалість механічного оброблення шихти складала від 1 до 25 хв зі швидкістю обертання барабана від 50 до 180 об/хв. Співвідношення маси шихти до маси тіл подрібнення (сталевих куль, діаметром 6 мм) становило 1 : 20 та 1 : 40. Дослідженнями визначено, що рекомендованим режимом механічної активації шихти Ti–C–Al–SiO₂–Al₂O₃–Fe₂O₃–ПТ-НА-01 є оброблення протягом 15 хв за швидкості обертання барабана 130 об/хв та співвідношення 1 : 40 маси шихти до маси сталевих куль. Гранулометричний склад шихти зменшується з максимального розміру 100 мкм до 40 мкм. На основі досліджень визначено, що таке оброблення шихти призводить до підвищення хімічної активності компонентів та ефективності протікання СВС-процесу внаслідок зниження тривалості його ініціювання та процесу синтезу.

The paper is devoted to one of the urgent problems of modern materials science – the creation of materials with predetermined properties, methods of their production and practical applica-tion. Goal. This work is devoted to the study of the influence of mechanical activation parameters on the synthesis duration and morphology of the Ti–C–Al–SiO₂–Al₂O₃–Fe₂O₃–ПТ-НА-01 charge intended for the production of a modifying composite material obtained by self-propagating high-temperature synthesis. Methodology. Powders Ti–C–Al–SiO₂–Al₂O₃–Fe₂O₃–ПТ-НА-01 are used as starting materials. Mechanical activation of the charge with variation of process parameters was carried out in a ball mill of the KM-1 model, developed by the authors of this work, of the intermittent principle of operation with a working steel drum volume of 1.5‧10⁻⁴m³. The ball mill weighs 5.8 kg and has dimensions (W-H-D) of 190-180-230 mm. The duration of mechanical processing of the charge was from 1 to 25 minutes, with a drum rotation speed of 50 to 180 rpm. The ratio of the charge weight to the grinding media weight (steel balls with a diameter of 6 mm) was 1 : 20 and 1 : 40. Results. Studies have established that the recommended mode of mechanical activation of the Ti–C–Al–SiO₂–Al₂O₃–Fe₂O₃–ПТ-НА-01 charge is treatment for 15 minutes at a drum rotation speed of 130 rpm and a ratio of 1:40 charge weight to steel ball weight. The particle size distribution of the charge is reduced from a maximum size of 100 microns to 40 microns. Originality. Based on the studies conducted, it can be concluded that such treatment of this charge leads to an increase in the chemical activity of the components and increases the efficiency of the SHS process by reducing the duration of its initiation and synthesis. Practical value. The developed modified composite material is recommended for arc surfacing and gas thermal spraying of strengthening and restoring coatings of machine parts.
Study of the influence of the parameters of the Ti–C–Al–SiO₂–Al₂O₃–Fe₂O₃–ПТ-НА-01 charge stock mechanical activation on the duration of the modifying composites synthesis
Keywords: механічна активація; хімічні елементи; шихта; самопоширюваний високотемпературний синтез; кульовий млин; композиційний матеріал; наплавлення; напилення; mechanical activation; chemical element; charge; self-propagating high-temperature synthesis; ball mill; composite material; surfacing; spraying